The design of digital automation technologies: Implications for the future of work - Maria Savona; Tommaso Ciarli; William Edward Steinmueller; Simone Vannuccini (EconPol Forum, 2022)
Automation technologies, including within the same family, are fundamentally heterogeneous in their design and the tasks they can execute. While the number of sectors that are exposed to most digital automation technologies is still relatively limited, it is expanding. Data-intensive technologies are more pervasive in services than in manufacturing sector. This calls for policy to extend its focus from robots to other, more pervasive, forms of automation. Robots are designed more to substitute workers than to complement them, while data-intensive technologies are consistently more complementary to humans
Keywords: 330